2017
DOI: 10.1186/s12885-017-3067-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of geographical differences in management and outcomes for colorectal cancer in Australia

Abstract: BackgroundAustralia and New Zealand have the highest incidence of colorectal cancer (CRC) in the world, presenting considerable health, economic, and societal burden. Over a third of the Australian population live in regional areas and research has shown they experience a range of health disadvantages that result in a higher disease burden and lower life expectancy. The extent to which geographical disparities exist in CRC management and outcomes has not been systematically explored. The present review aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 53 publications
(46 reference statements)
1
45
0
Order By: Relevance
“…A systematic review of differences by place of residence in clinical management and outcomes for colorectal cancer patients in Australia found worse survival for patients who lived outside major cities . Some of the reviewed factors appeared to explain part of the observed differences in survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of differences by place of residence in clinical management and outcomes for colorectal cancer patients in Australia found worse survival for patients who lived outside major cities . Some of the reviewed factors appeared to explain part of the observed differences in survival.…”
Section: Discussionmentioning
confidence: 99%
“…The World Bank Data 2014 was used to identify high‐income nations . We expanded our search by reviewing the bibliographies of all eligible studies and related reviews . We also conducted a search using Google Scholar to identify potentially eligible studies that might not have been detected through the above process.…”
Section: Methodsmentioning
confidence: 99%
“…Among patients with metastatic CRC, median survival in Greenland was similar to patients in Scandinavia: 17 vs. 15.8 months for patients treated with chemotherapy and 2 vs. 2.8 months for patients receiving best supportive care alone [20]. Despite a previous study in Greenland suggesting a significant diagnostic delay for patients living in remote areas outside Nuuk [6], and international research reporting on significant disparities in cancer-related outcomes in rural and remote areas [1013], we found no significant difference in stage distribution or survival rates between patients from Nuuk and patients living along the coastline outside Nuuk.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a recent study in Greenland evaluating 113 CRC patients indicated that patients living on the coastline were exposed to a significant diagnostic delay compared to their counterparts in Nuuk [9]. Geographical remoteness has also been shown to cause disparities in treatment patterns and outcome for cancer patients living in Australia, USA and Canada [1013]. Globally, survival is generally better in countries with good access to specialised care [14].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) or bowel cancer is the most common cancer for men and women combined and is the second leading cause of cancer death in Australia 5 . Our systematic review showed that people with CRC living in non‐metropolitan Australia have poorer survival rates compared to those living in metropolitan areas 6 . Although this may be due to an interplay of numerous personal, community and health system influences, evidence suggests early detection may play an important role 7,8 .…”
mentioning
confidence: 86%